Variasi Karakter Morfologi Cyrtodactylus marmoratus Gray, 1831 (Reptilia: Squamata: Gekkonidae) dari Pulau Jawa - Wiradarma, Huda; Baskoro, Karyadi; Hadi, Mochamad; Hamidy, Amir; Riyanto, Awal (Bioma : Berkala Ilmiah Biologi, 2019)
Cyrtodactylus marmoratus is one of the first species described by Gray in 1831 on the island of Java that believed to have a variation of morphologic characters that not yet complete to revealed. This research aimed to develop any variation characters possessed by Cyrtodactylus marmoratus. The character morphology, morphometric, and meristic follow the statement of Hartmann (2016). Data were collected in August to November in the Lab. Herpetology MZB (Museum Zoologicum Bogoriense) LIPI (The Indonesian Institute of Sciences). Variation characters possessedÂ  by Cyrtodactylus marmoratus, there are 4 Characters Morphology: Head Morph (HM), Patern Morph on the Body (PtrM), Post Cloacal Tubercles (PCT), and second post mental (PM2); a Morphometry Characters is snout-vent Length (SVL); and 12 characters Meristic are: Precloacal Pores (PP), Precloaco-femoral Pores (PFP), Enlarged Precloaco-femoral Scales (EPFS), Ventral Scales (VS), Paravertebral Tubercles (PVT), Dorsal Tubercles (DTR), Lamella Under Toe-IV (LT4), Lamella Under Toe-V (LT5), Lamella Under Finger-III (LF3), Lamella Finger-IV (LF4), Femoral Pores Left (FPL), Femoral Pores Right (FPR).